Dampak Pandemi Covid-19 dalam Hukum Ketenagakerjaan di Wilayah Yogyakarta - Elza Qorina Pangestika; Fifink Praiseda Alviolit; Hartanto Hartanto; Bagus Anwar Hidayatulloh (Journal on Education, 2022)
At the end of 2019, the world was shocked by the existence of a new condition, namely the Covid-19 pandemic. In almost two years, the Indonesian government has issued various policies during the Covid-19 pandemic. One of these policies is a prohibition on people gathering and doing activities outside the home, and a recommendation to stay at home. This government policy of course also has an impact on wider sectors, one of which is the employment sector. The employment sector is one of the sectors affected by government policies during the pandemic, because employment is closely related to the economy and industry, many entrepreneurs have had their income reduced because people's consumption power has decreased, and this has a more serious impact on their workers. This research aims to find out the impact of the Covid-19 pandemic on employment law in the Yogyakarta area. The subjects of this research are workers who were affected during the Covid-19 pandemic in the Yogyakarta area and resource persons who are experts in labor law. After this research was carried out, we now know the impact of the Covid-19 pandemic on employment law in the Yogyakarta area.